1992
DOI: 10.1099/0022-1317-73-9-2441
|View full text |Cite
|
Sign up to set email alerts
|

Sequence comparison between the phosphoprotein mRNAs of human and bovine respiratory syncytial viruses identifies a divergent domain in the predicted protein

Abstract: The nucleotide and deduced amino acid sequences of the phosphoprotein (P) mRNA of bovine respiratory syncytial virus (BRSV) strain A51908 have been determined. The P mRNA is 860 nucleotides long with a single large open reading frame and the encoded polypeptide is 241 amino acids long. Comparison with the corresponding sequences of human respiratory syncytial virus (HRSV) subgroups A and B revealed 72 to 74% identity at the nucleotide level, and 81% at the amino acid level. The P protein contains a single dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Thus, all of the identified epitopes correspond to regions that are indicated to be antigenic by various criteria used for the prediction of both the surface exposure and secondary structure of proteins. Our ELISA data confirm earlier observations (McIntosh & Chanock, 1985;Collins, 1991) concerning the abundance of anti-P protein antibodies in HCS from RSV-infected persons and revealed the antibody response targets to lie within three conserved (Mallipeddi & Samal, 1992) regions of the P protein molecule. Moreover, EL1SA competition data (data not shown) demonstrated that RSV-positive HCS contained antibodies directed against each of two antigenic determinants (represented by peptide antigens, i.e.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, all of the identified epitopes correspond to regions that are indicated to be antigenic by various criteria used for the prediction of both the surface exposure and secondary structure of proteins. Our ELISA data confirm earlier observations (McIntosh & Chanock, 1985;Collins, 1991) concerning the abundance of anti-P protein antibodies in HCS from RSV-infected persons and revealed the antibody response targets to lie within three conserved (Mallipeddi & Samal, 1992) regions of the P protein molecule. Moreover, EL1SA competition data (data not shown) demonstrated that RSV-positive HCS contained antibodies directed against each of two antigenic determinants (represented by peptide antigens, i.e.…”
Section: Discussionsupporting
confidence: 80%
“…The peptides reacted with MAbs and with a panel of 20 RSV-positive sera samples derived from convalescing patients. All three sites are localized within three conserved regions of the P protein (Mallipeddi & Samal, 1992), i.e. Pro91-Asp110, SerlG 1 Lys~s 0 and Glu221 Phe2av Within these regions the epitope dependence on individual amino acids was determined.…”
Section: Introductionmentioning
confidence: 99%
“…As ovine and bovine RSV strains were found to be antigenically related by indirect immunofluorescence and virus neutralization tests, the potential for interspecies transmission of the virus between cattle, sheep and goats could not be ruled out (Lehmkuhl et al, 1980). Several analyses on the molecular organization of the bovine RSV have been performed (Lerch et al, 1989;Walravens et al, 1990;Samal & Zamora, 1991;Mallipeddi & Samal, 1992). Sequence comparison between proteins from bovine and human RSV showed that the G and small hydrophobic (SH) proteins are least conserved (30 and 38% identity, respectively; Lerch et al, 1990;Samal & Zamora, 1991).…”
Section: Analysis Of the Ovine Respiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…The nucleotide and deduced amino acid sequences of nine mRNAs of BRSV and the intergenic sequences of all the genes of BRSV have been determined Zamora & Samal, 1992 a, b ;Mallipeddi & Samal, 1992 ;Pastey & Samal, 1995 ;Walravens et al, 1990 ;Lerch et al, 1990). Comparison of the deduced amino acid sequences of these BRSV proteins to those of their counterparts in HRSV subgroup A showed the following percentage identities : nonstructural protein 1 (NS1), 69 % ; nonstructural protein 2 (NS2), 84 % ; nucleocapsid protein (N) 93 % ; phosphoprotein (P), 81 % ; matrix protein (M), 89 % ; small hydrophobic protein (SH), 38 % ; glycoprotein (G), 30 % ; fusion protein (F), 81 % ; and M2 protein, 80 %.…”
Section: Introductionmentioning
confidence: 99%